Exploring API-driven business models: Lessons learned from Amadeus's digital transformation - Saeid Heshmatisafa; Marko Seppänen (Digital Business, 2023)
Digital transformation compels companies to seek new strategies and business models, allowing firms to find new ways to create and capture value. APIs have been widely used in improving internal processes and have been opened up recently to third-party developers to enable innovations in digital ecosystems. However, few studies have documented success stories of value generation through employing public APIs and thus enabling new, API-driven business models. This single case study examined the digital transformation in one of the leading organizations of the travel industry, Amadeus Corporation. Publicly available documents and other gray literature were used as data for content analysis. The results show how Amadeus has transformed its business model into an API-driven business model. This study contributes to the literature on API-driven business models by demonstrating the implication of APIs as a strategic tool in value co-creation. We identified six different values that were generated by exposing digital assets to API consumers through the API-driven business models of self-service platforms: commercialization, ecosystem, big data, market and marketplace, entrepreneurship, and R&D.